Ni speciation in tea infusions by monolithic chromatography—ICP-MS and Q-TOF-MS - Ščančar, Janez; Zuliani, Tea; Žigon, Dušan; Milačič, Radmila (Analytical and bioanalytical chemistry, 2013)
For humans, Ni is not considered to be an essential trace element. Its compounds, at levels present in foodstuffs and drinks, are generally considered to be safe for consumption, but for individuals who already suffer from contact allergy to Ni and may be subject to develop systemic reactions from its dietary ingestion, dietary exposure to Ni must be kept under control. Being the second most popular beverage, tea is a potential source of dietary Ni. Present knowledge on its speciation in tea infusions is poor. Therefore, complete speciation analysis, consisting of separation by liquid chromatography using a weak CIM DEAE-1 monolithic column, “on-line” detection by inductively coupled plasma mass spectrometry (ICP-MS) and “off-line” identification of ligands by hybrid quadrupole time-of-flight mass spectrometry (Q-TOF MS), was implemented for the first time to study Ni speciation in tea infusions. Total concentrations of Ni in dry leaves of white, green, oolong and black tea ( Camellia sinensis ) and flowers of herbal chamomile ( Matricaria chamomilla ) and hibiscus ( Hibiscus sabdariffa ) tea were determined after microwave digestion by ICP-MS. They lay between 1.21 and 14.4 mg kg −1 . Good agreement between the determined and the certified values of the Ni content in the standard reference material SRM 1573a tomato leaves confirmed the accuracy of the total Ni determination. During the infusion process, up to 85 % of Ni was extracted from tea leaves or flowers. Separation of Ni species was completed in 10 min by applying aqueous linear gradient elution with 0.6 mol L −1 NH 4 NO 3 . Ni was found to be present in the chromatographic fraction in which quinic acid was identified by Q-TOF in all the tea infusions analysed, which had pH values between 5.6 and 6.0. The only exception was the infusion of hibiscus tea with a pH of 2.7, where results of speciation analysis showed that Ni is present in its divalent ionic form.